2022
DOI: 10.1007/s11229-022-03514-3
|View full text |Cite
|
Sign up to set email alerts
|

Robust passage phenomenology probably does not explain future-bias

Abstract: People are ‘biased toward the future’: all else being equal, we typically prefer to have positive experiences in the future, and negative experiences in the past. Several explanations have been suggested for this pattern of preferences. Adjudicating among these explanations can, among other things, shed light on the rationality of future-bias: For instance, if our preferences are explained by unjustified beliefs or an illusory phenomenology, we might conclude that they are irrational. This paper investigates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…No study has found that beliefs about the metaphysics of time or temporal phenomenology alone contribute to future-bias. While Latham et al (2021b) found that people showed less future-bias when presented with a description of our world as lacking rather than containing robust temporal passage, people's actual beliefs about whether time passes had no discernible effect on future-bias. They hypothesised that exposure to 'moving time'/'moving ego' language might tend to elicit a certain sort of temporal phenomenology that contributes to future-bias, which would support the temporal phenomenology hypothesis.…”
Section: What Empirical Work Reveals About Normative Theorisingmentioning
confidence: 75%
See 3 more Smart Citations
“…No study has found that beliefs about the metaphysics of time or temporal phenomenology alone contribute to future-bias. While Latham et al (2021b) found that people showed less future-bias when presented with a description of our world as lacking rather than containing robust temporal passage, people's actual beliefs about whether time passes had no discernible effect on future-bias. They hypothesised that exposure to 'moving time'/'moving ego' language might tend to elicit a certain sort of temporal phenomenology that contributes to future-bias, which would support the temporal phenomenology hypothesis.…”
Section: What Empirical Work Reveals About Normative Theorisingmentioning
confidence: 75%
“…They hypothesised that exposure to ‘moving time’/‘moving ego’ language might tend to elicit a certain sort of temporal phenomenology that contributes to future‐bias, which would support the temporal phenomenology hypothesis. But in a follow‐up study (Latham et al., 2021c), they found no association between self‐reported moving time or moving ego phenomenology and future‐bias.…”
Section: What Empirical Work Reveals About Normative Theorisingmentioning
confidence: 92%
See 2 more Smart Citations
“…2 Many dynamists 3 and some non-dynamists 4 have thought that a dynamical account of time better accords with our 'ordinary' view of time. Empirical evidence suggests that many of us (at least amongst the sample of US residents tested) have a 'naïve' (i.e., pre-theoretical) representation of time that is closer to dynamical than non-dynamical (e.g., Latham et al, 2019Latham et al, , 2020aLatham et al, 2021aLatham et al, , 2021bLatham et al, , 2021cHodroj, Latham, Lee-Tory and Miller forthcoming;Baron, Everett, Latham, Miller, Tierney and Oh ms). Latham Miller and Norton (2021a, 2020a, 2020b) used detailed vignettes that described a variety of different dynamical and non-dynamical models of time, and asked participants which they think is most like our universe.…”
Section: Introductionmentioning
confidence: 99%